Partial Carpal Arthrodesis in the Horse - Auer, J. A.; Taylor, J. R.; Watkins, J. P.; Welch, R. D.; Stricklin, J. B. (Veterinary and Comparative Orthopaedics and Traumatology, 1990)
Over a period of 6 years, four horses and two foals were treated with partial carpal arthrodesis. The problems treated included one luxation each of the carpometacarpal, and the antebrachiocarpal joint, as well as one subluxation of the carpometacarpal and the middle carpal joints. The luxations developed secondary to rupture of the joint capsule as well as one or two collateral ligaments. In three cases, comminuted fractures of the distal row of carpal bones, complicated in one of these cases by a fracture of the intermediate carpal bone, were treated. Arthrodesis by internal fixation using T-plates or dynamic compression plates of various sizes was successful in salvaging some of the animals. The various cases are discussed in detail as to technique and reason of its application. One horse was euthanatized, two are presently used for pleasure riding and three horses are used for breeding purposes. The horses treated by means of arthrodesis were compared to one case of luxation of the middle carpal joint, which was treated unsuccessfully by external coaptation alone.The results of partial carpal arthrodesis in four horses and two foals are described, as are the techniques employed and the results.
Keywords: Carpus; Fractures, comminuted; Luxations; Collateral ligament rupture; Arthrodesis; Internal fixation; Salvage procedure